Fabrication of zinc oxide/sodium alginate nanocomposite for effective catalytic degradation of Direct Yellow 44 dye: A sustainable approach - Shumaila Kiran; Abdulaziz Bentalib; Alina Javaid; Mubashar Hussain; Muhammad Wakil Shahzad; Zubair Khaliq; Muhammad Bilal Qadir; Zaryab Rashid (Desalination and Water Treatment)
Environmental pollution associated with the discharge of industries is becoming a global concern. Textile dyes indicate some of the most complex environmental pollutants due to their complexity and variety. It has also been shown that nanotechnology is the best and most modern approaches for removing dyes. Nanocomposites are used as adsorbents for the removal of pollutants from water. This research chemically synthesized the zinc oxide/sodium alginate (ZnO/SA) nanocomposite. The synthesized nanocomposite was analyzed by UV-Visible spectroscopy, SEM, XRD and FTIR techniques. The prepared nanocomposite was used to degrade Direct Yellow 44 dye after optimizing various experimental factors (temperature, pH, H2O2, nanocomposite level, and dye level). The maximum decolorization (78.1 %) was seen at 0.01 % dye concentration, 5 mg/mL ZnO/SA nanocomposite concentration, pH 5, H2O2 concentration 0.04 mM, at 40 °C. Optimized reaction parameters were applied to textile industrial effluent using ZnO/SA nanocomposite. Maximum decolorization (44.3 %) for the inlet and outlet textile industrial effluent (50.5 %) was found at 60 minutes. Treated samples were evaluated using different quality assurance measures like pH, TDS, TSS, COD, TOC, etc. It has been observed that the reduction (%) values of COD and TOC were seen to be 74.2 % and 71.1 %, respectively. Catalyst reusability was also evaluated.